Affiliate marketing, live streaming, and impulsive buying: evidence from generation Z TikTok consumers - Prasetyo, Johan Hendri; Ariawan, Joko; Wiharso, Gani; Basudani, Wahid Akbar (Institute of Computer Science (IOCS), 2025)
In the rapidly expanding digital economy, businesses increasingly rely on online promotional tools to attract and retain customers. This study investigated the effect of affiliate marketing on consumer purchase decisions. Grounded in consumer behavior and digital marketing theories, the research aimed to understand how affiliate marketing strategies influence purchasing behavior in online environments. A quantitative approach was employed using a structured questionnaire distributed to online shoppers who had interacted with affiliate marketing content. Data were analyzed using multiple regression analysis to examine the relationship between affiliate marketing and purchase decision variables. The findings revealed that affiliate marketing had a significant and positive influence on consumer purchase decisions. The results indicated that effective affiliate strategies, such as personalized recommendations and transparent product reviews, increased consumer trust and purchase intention. Theoretically, the study contributed to the development of digital marketing literature by confirming the role of affiliate strategies in shaping online consumer decision-making. Practically, the results provided insights for marketers to design more credible and targeted affiliate campaigns that enhance consumer engagement and conversion rates. It was concluded that affiliate marketing served as an important promotional tool that shaped consumer decision-making patterns in the digital marketplace. Future studies were suggested to explore the role of influencer credibility and technological innovation in strengthening the impact of affiliate marketing.